MANAJEMEN PEMBIAYAAN STRATEGIS DI MADRASAH TSANAWIYAH: MENINGKATKAN KELESTARIAN PROGRAM EKSTRAKURIKULER MELALUI TATA KELOLA PARTISIPATIF - Aziz, Abdul; Masrurah, Waqiatul (Islamic Education Management Study Program, Tarbiyah and Teacher Training Faculty, State Islamic University of Madura, 2025)
Strategic financial management in Islamic educational institutions is grounded in the principles of participatory governance, where transparency, accountability, and stakeholder collaboration ensure the sustainable allocation and utilization of resources for holistic student development. This study aims to analyze the financial management of extracurricular activities at MTs Miftahul Ulum Pagendingan, using the POAC (Planning, Organizing, Actuating, Controlling) framework and stakeholder participation theory. The research employed a qualitative approach, with data collected through observation, in-depth interviews, and documentation. Findings indicate that budget planning is conducted collaboratively among the principal, student affairs vice principal, treasurer, and extracurricular advisors based on activity needs. Organizing involves clear role distribution among relevant units, while funding sources include School Operational Assistance (Bantuan Operasional Sekolah/BOS), parental contributions, and voluntary donations. Financial control is maintained through periodic evaluations and transparent financial reporting. Key enablers include active involvement of all stakeholders, whereas major constraints consist of limited funding and low parental awareness. Strengthening strategies involve optimizing funding sources, enhancing budget transparency, and improving communication and collaboration with stakeholders. The study concludes that accountable and participatory financial management is essential to ensuring the long-term sustainability of extracurricular programs in Islamic junior high schools.